2013
DOI: 10.5389/ksae.2013.55.3.091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indirect Wastewater Reuse on Water Quality and Soil Environment in Paddy Fields

Abstract: The objectives of this study were to monitor and assess the environmental impacts of indirect wastewater reuse on water quality and soil in paddy fields. Yongin monitoring site (YI) irrigated from agricultural reservoir and Osan monitoring site (OS) irrigated with treated wastewater diluted with stream water were selected as control and treatment, respectively. Monitoring results for irrigation water quality showed a significant statistical difference in salinity, exchangeable cation and nutrients. Pond water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Even for sites irrigated by relatively clean water derived from a reservoir, an average of about 15,700 MPN/100 mL of total coliform was detected [20]. It was also found that the total coliform of the irrigation water containing untreated wastewater was about 77,000 MPN/100 mL [21].…”
Section: Coliform Bacteriamentioning
confidence: 79%
See 4 more Smart Citations
“…Even for sites irrigated by relatively clean water derived from a reservoir, an average of about 15,700 MPN/100 mL of total coliform was detected [20]. It was also found that the total coliform of the irrigation water containing untreated wastewater was about 77,000 MPN/100 mL [21].…”
Section: Coliform Bacteriamentioning
confidence: 79%
“…This indicates that the subjected level of total coliform can be easily found in nature and is inadequate as an indicator for microbes. The E. coli concentration of irrigation water with high levels of total coliform concentration was measured to be 13, 46, and 107 MPN/100 mL for reservoir water, indirect wastewater reuse water, and irrigation water containing untreated wastewater, respectively [20,21]. For fecal coliform, the concentrations for the subjects above were 5000, 180, and 633 MPN/100 mL, respectively [20,21].…”
Section: Coliform Bacteriamentioning
confidence: 99%
See 3 more Smart Citations